Implementation of Inclusivism Values in Religious Education Learning to Build Human Solidarity at Karuna Dipa High School, Palu - Rusmin, Rusmin; Hamka, Hamka; Ahmad Syahid (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2024)
This research examines the implementation of inclusivism values ​​in religious education learning to build humanitarian solidarity at Karuna Dipa High School, Palu. This research uses qualitative methods, and data is collected through observation, in-depth interviews, and analysis of written documents. The data analysis techniques used are data reduction, presentation, and verification. The research results show that: First, the values ​​of inclusivism are the basic principles at Karuna Dipa High School Palu, namely Inclusive (open) values, tolerance values, mutual help values, justice values, and brotherhood values ​​(humanism). Second, the implementation of inclusivist values ​​in religious education learning at Karuna Dipa Palu High School follows the inclusive religious education learning model from Jack L. Seymour and Tabita K. Cristiani, namely the